Prevalence and Mental Health Correlates of Insomnia in First-Encounter Veterans with and without Military Sexual Trauma - Jenkins, Melissa M. (Sleep, 2015)
STUDY OBJECTIVES: There is limited information about prevalence of insomnia in general populations of veterans of recent wars in Iraq and Afghanistan. No studies have examined insomnia in veterans with military sexual trauma (MST). We assess prevalence of insomnia, identify types of services sought by veterans with insomnia, and examine correlates of insomnia in veterans with and without MST. DESIGN: A cross-sectional study of first-encounter veterans registering to establish care. SETTING: Veteran Affairs San Diego Healthcare System. PARTICIPANTS: Nine hundred seventeen veterans completed questionnaires assessing insomnia, MST, service needs, traumatic brain injury, resilience, and symptoms of depression, posttraumatic stress disorder (PTSD), pain, alcohol misuse, and hypomania. INTERVENTIONS: N/A. MEASUREMENTS AND RESULTS: 53.1% of veterans without MST and 60.8% of veterans with MST had clinically significant insomnia symptoms, with the MST subsample reporting more severe symptoms, P < 0.05. Insomnia was more prevalent than depression, hypomania, PTSD, and substance misuse. Veterans with insomnia were more likely to seek care for physical health problems and primary care versus mental health concerns, P < 0.001. For the veteran sample without MST, age, combat service, traumatic brain injury, pain, and depression were associated with worse insomnia, P < 0.001. For the MST subsample, employment status, pain, and depression were associated with worse insomnia, P < 0.001. CONCLUSIONS: Study findings indicate a higher rate of insomnia in veterans compared to what has been found in the general population. Insomnia is more prevalent, and more severe, in veterans with military sexual trauma. Routine insomnia assessments and referrals to providers who can provide evidence-based treatment are crucial. CITATION: Jenkins MM, Colvonen PJ, Norman SB, Afari N, Allard CB, Drummond SP. Prevalence and mental health correlates of insomnia in first-encounter veterans with and without military sexual trauma. SLEEP 2015;38(10):1547–1554.